Arabic Character Recognition Using Fractal Dimension - Khalil Alsaif; Karam Thanoon (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this work the concepts of the pattern recognition was used to recognize printed Arabic characters, and the Fractal geometric dimension method was used. The input for the system is image, with bitmap format , then the image of character is recognized, and after that it is feeding to the OCR system. A feature space containing the values of the fractal dimension for the letters of Arabic was constructed. These features were used in the recognition phase. In this phase a comparison was made between the values in the feature space and the values of the letter inputs to be recognized, the comparison was done by the minimum Euclidian distance. Results of this work are 75% succeeded. And Matlab 6.5 is used to write the functions and subroutines for this work.